Ubiquitous Learning Environments and Language Mastery: Designing Adaptive Platforms for 21st-Century Language Learners - Nur Hakim; Samuel Tuan; Esther Allen (International Journal of Language and Ubiquitous Learning, 2026)
Background. Ubiquitous learning environments (ULEs) have become a cornerstone in modern education, driven by the increasing use of digital technologies and mobile devices. These environments allow for continuous learning, enabling students to engage with educational content anytime and anywhere. In the context of language learning, ULEs present unique opportunities to enhance language mastery by providing adaptive, context-aware platforms that cater to the dynamic needs of 21st-century learners. However, the design and implementation of such platforms remain underexplored, particularly in how they can be optimized for language acquisition. Purpose. This study aims to design and evaluate adaptive language learning platforms within ubiquitous learning environments that support the development of language mastery. The research focuses on creating a dynamic platform that adjusts to learners’ needs, context, and progress, thereby fostering an engaging and personalized learning experience. Method. The study uses a mixed-methods approach, combining the design of a prototype adaptive language learning platform with empirical data collection from language learners using the platform. Participants’ language proficiency, engagement, and learning outcomes were assessed through pre- and post-tests, usage analytics, and surveys. Results. omes were assessed through pre- and post-tests, usage analytics, and surveys. The findings indicate that learners using the adaptive platform demonstrated significant improvements in language proficiency, particularly in speaking and listening skills. Additionally, learners reported higher engagement and satisfaction levels compared to traditional language learning methods. Conclusion. Adaptive platforms in ubiquitous learning environments can significantly enhance language learning outcomes by providing personalized and flexible learning experiences. Future research should focus on further optimizing these platforms for diverse learner populations.